Self-Replicating Cracks: A Collaborative Fracture Mode in Thin Films - Melo-Hurtado, F (American Physical Society, 2014)
Straight cracks are observed in thin coatings under residual tensile stress, resulting into the classical network pattern observed in china crockery, old paintings, or dry mud. Here, we present a novel fracture mechanism where delamination and propagation occur simultaneously, leading to the spontaneous self-replication of an initial template. Surprisingly, this mechanism is active below the standard critical tensile load for channel cracks and selects a robust interaction length scale on the order of 30 times the film thickness. Depending on triggering mechanisms, crescent alleys, spirals, or long bands are generated over a wide range of experimental parameters. We describe with a simple physical model, the selection of the fracture path and provide a configuration diagram displaying the different failure modes. © 2014 American Physical Society.